Correlation Between Follicle Stimulating Hormone, Anti-Müllerian Hormone and Antral Follicle Count with Different Age Groups in Infertile Women - Bhowmik, Juthi; Fatima, Parveen; Banu, Jesmine; Deeba, Farzana; Chowdhury, Sheuli; Isharat, Shakeela (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Reduced ovarian reserve predicts poor ovarian response and poor suc– cess rates in infertile women who undergo Assisted Reproductive Technology (ART). Ovarian reserve decreases with age but the rate of decline varies from one woman to another. Follicle Stimulating Hormone (FSH) Anti-Müllerian Hormone (AMH) and antral follicle count (AFC) represent the three most frequently utilized laboratory tests in determining Ovarian Reserve (OR). To determine correlation between FSH, AMH and AFC in infertile female. Materials and methods: It was an observational (Cross sectional) study. This study was done in the Department of Reproductive Endocrinology and Infertility, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, between July 2018 to June 2019. The study population consisted of all the diagnosed female infertility patients of reproductive age. The women attending the study center during study period having primary or secondary infertility was considered as study population. They were divided in 4 age groups 21-25, 26-30, 31-35 yrs and 36-40 yrs years. Data was collected using a structured questionnaire following physical & lab examination. For D2 FSH level fasting blood was collected on D2/3 of menstrual cycle, serum FSH level was measured by ADVIA Centraur(R) XP immunoassay system. For S. AMH level blood sample was collected on 2nd day of cycle and measured by BECKMAN COULTER machine using Chemiluminescent Immunoassay method. For AFC count TVS was done on D2-5 of cycle using KONTRON medical USG machine. Collected data were classified, edited, coded and entered into the computer for statistical analysis by using SPSS version 23. Results: Out of 74 patients the mean age was found 32.6±5.5 years. Serum FSH, AMH and AFC were significantly associated with different age group. A negative correlation was found between serum FSH and serum AMH in all age group. But strong correlation found in age group 31-35 yrs and in 36-40 years age group. A negative correlation was found between serum FSH and total AFC in age group 26- 30 years, 31-35 years and 36-40 years respectively. A positive correlation was found between serum AMH and total AFC in all age group but most strong in age group 31-35 years. In multivariate logistic regression analysis serum AMH (<1.0 ng/ml) and total AFC (<5 number) were found to be significantly associated with age group >35 years patients. Conclusion: In all age grqoup, FSH, AMH and AFC correlates but it is more pronounced in advanced age that means >35 years age group. Chatt Maa Shi Hosp Med Coll J; Vol.20 (1); January 2021; Page 22-27